Twin Chorionicity and the Risk of Hypertensive Disorders: Gestational Hypertension and Pre-eclampsia. (10th May 2016) - Bartnik, Pawel; Kosinska-Kaczynska, Katarzyna; Kacperczyk, Joanna; Ananicz, Wojciech; Sierocińska, Aleksandra; Wielgos, Miroslaw; Szymusik, Iwona
Abstract : Twin gestation is known to be a risk factor for hypertensive disorders of pregnancy. However, the relationship between hypertensive disorders (pre-eclampsia (PE) and gestational hypertension (GH)) and chorionicity of twin pregnancy is unclear, and published data is conflicting. We decided to analyze the relationship between placentation and prevalence of hypertensive disorders. It was a retrospective cohort study. 312 twin pregnancies delivered between 2009 and 2014 were analyzed, 79 of which were monochorionic and 233 dichorionic. The occurrence of PE and GH was established according to American College of Obstetricians and Gynecologists' (ACOG) guidelines. Hypertensive disorders were diagnosed significantly more often in dichorionic than in monochorionic twin pregnancies (19.7% vs. 8.9%; OR = 2.53 95% CI 1.04–6.45; p = .03). PE occurred more frequently in DCP (13.3% vs. 3.8%; OR = 3.88 95% CI 1.09–16.46; p = .02). There were no differences between those two groups in the prevalence of GH (6.4% vs. 5.1%; p = .79). The logistic regression model for the occurrence of PE included chorionicity, mother's age lower than 18 or higher than 40, pre-gestational obesity, in vitro fertilization, primiparity, gestational age at delivery, gestational diabetes, and active smoking. It showed that dichorionicity remained an independent risk factor for PE (adjusted OR = 4.97.0 95% CI 1.06–23.38; p = .04). Dichorionicity seems to be a risk factor for PE but not for GH development.